Thalamocortical Afferents Innervate the Cortical Subplate much Earlier in Development in Primate than in Rodent - Alzu’bi, Ayman (Cereb Cortex, 2019)
The current model, based on rodent data, proposes that thalamocortical afferents (TCA) innervate the subplate towards the end of cortical neurogenesis. This implies that the laminar identity of cortical neurons is specified by intrinsic instructions rather than information of thalamic origin. In order to determine whether this mechanism is conserved in the primates, we examined the growth of thalamocortical (TCA) and corticofugal afferents in early human and monkey fetal development. In the human, TCA, identified by secretagogin, calbindin, and ROBO1 immunoreactivity, were observed in the internal capsule of the ventral telencephalon as early as 7–7.5 PCW, crossing the pallial/subpallial boundary (PSB) by 8 PCW before the calretinin immunoreactive corticofugal fibers do. Furthermore, TCA were observed to be passing through the intermediate zone and innervating the presubplate of the dorsolateral cortex, and already by 10–12 PCW TCAs were occupying much of the cortex. Observations at equivalent stages in the marmoset confirmed that this pattern is conserved across primates. Therefore, our results demonstrate that in primates, TCAs innervate the cortical presubplate at earlier stages than previously demonstrated by acetylcholinesterase histochemistry, suggesting that pioneer thalamic afferents may contribute to early cortical circuitry that can participate in defining cortical neuron phenotypes.